PROBLEMS OF SOCIALIZATION OF PERSONALITY IN THE SYSTEM OF SOCIAL STRATEGY - Djurayev Avaz Akhmedjanovich (Journal Park Publishing, 2024)
This article presents an analysis of modern problems of personal socialization in the context of social strategy. It highlights the influence of various aspects of social strategy, such as education, economic policy, media and cultural influences, political context, and gender and ethnic aspects, on the process of socialization of an individual. The article highlights the challenges that modern societies face in ensuring effective socialization, and suggests possible strategies for solving these problems, taking into account the characteristics of a specific social environment. As a result, the article calls for a deeper understanding and active participation in the process of forming a social strategy in order to ensure the successful socialization of the individual in modern society.
Keywords: socialization, personality, social strategy, education, cultural influences, political context.